Companion to music in the age of the Catholic monarchs - Knighton, Tess, 1957- (Brill's companions to the musical culture of medieval and early modern Europe, 2016)
The 'Companion to Music in the Age of the Catholic Monarchs', edited by Tess Knighton, offers a major new study that deepens and enriches our understanding of the forms and functions of music that flourished in late medieval Spanish society. The fifteen essays, written by leading authorities in the field, present a synthesis based on recently discovered material that throws new light on different aspects of musical life during the reign of Ferdinand and Isabel (1474-1516): sacred and secular music-making in royal and aristocratic circles; the cathedral music environment; liturgy and power; musical connections with Rome, Portugal and the New World; theoretical and unwritten musical practices; women as patrons and performers; and the legacy of Jewish musical tradition.